Climatic niche shifts in 815 introduced plant species affect their predicted distributions. Issue 8 (10th June 2021) - Zachariah Atwater, Daniel; Barney, Jacob N.
Abstract: Aim: Introduced species often occupy different climates in their introduced than their native range, but to what degree do such 'climatic niche shifts' interfere with our ability to predict invasions? Answering this question is crucial if we are to understand the threat invasive species pose to human and natural systems, especially given the ever increasing use of species distribution models as tools for invasive species risk assessment and management. Here we investigated the degree to which climatic niche shifts interfered with the transferability of native‐ and introduced‐range species distribution models. Location: Our dataset consisted of c . 14 million occurrences distributed worldwide. Time period: Occurrence data were collected from online repositories dating from c . 1600 with the vast majority being from the 20th century. Climatic data represent means between 1970 and 2000. Major taxa studied: Our database represented 815 terrestrial plant species. Methods: We used ordination to identify climatic niche shifts as species moved between continents. Next, we trained separate Maxent models using native‐ or introduced‐range occurrences, and projected those models into each species' introduced range. We compared the ordination and Maxent models to determine whether niche shifts were associated with errors in Maxent predictions. Results: Models trained on native‐range occurrences poorly predicted introduced‐range occurrences, and transferability was lowest in species with large climatic niche shifts. Directional shifts in species' predicted geographic distributions mirrored their niche dynamics. This is concerning because native‐range data are often used to predict introduced‐range distributions. Main conclusions: Our results highlight the importance of considering niche shifts when modelling the potential geographic distributions of introduced species, and cast doubt on the assumption that the climatic niche of a species can be transferred between native and invasive ranges.